Prospective longitudinal study on prognostic factors of visual recovery and structural change after a first episode of optic neuritis. (17th June 2022) - Deschamps, Romain; Shor, Natalia; Vignal, Catherine; Guillaume, Jessica; Boudot de la Motte, Marine; Salviat, Flore; Lecler, Augustin; Marignier, Romain; Hage, Rabih; Coulette, Sarah; Bidot, Samuel; Gueguen, Antoine; et al.
Abstract: Background and purpose: This study was undertaken to determine the role of optical coherence tomography (OCT) in predicting the final visual and structural outcome, and to evaluate the correlation between functional eye outcome and retinal changes, in patients with a first episode of optic neuritis (ON). Methods: In this prospective study, consecutive adult patients with acute ON underwent ophthalmological evaluation at baseline and at 1 and 12 months, including OCT measurements of peripapillary retinal nerve fiber layer (pRNFL), macular ganglion cell and inner plexiform layer, and inner nuclear layer thicknesses; high‐ and low‐contrast visual acuity; visual field assessment; and baseline brain magnetic resonance imaging . Univariate and multivariate linear regressions were used to assess predictive factors of outcome. Correlations between 12‐month visual function and retinal structure were estimated by Spearman coefficients. Two groups of patients were analyzed, with or without multiple sclerosis (MS). Results: Among 116 patients, 79 (68.1%) had MS, and 37 (31.9%) had ON not related to MS (including 19 idiopathic [i.e., isolated] ON, and 13 and five with myelin oligodendrocyte glycoprotein and aquaporin‐4 antibodies, respectively). We found no independent predictive factor of visual and retinal outcome. Analysis of the relationship between the visual field test (mean deviation) and pRNFL thickness demonstrated a threshold of 75.4 μm and 66.4 μm, below which the mean deviation was worse, for patients with MS ( p  = 0.007) and without MS ( p  < 0.001), respectively. Conclusions: We found that inner retinal layer measurements during the first month are not predictive of final outcome. The critical threshold of axonal integrity, below which visual function is damaged, is different between patients with and without MS. Abstract : The critical threshold of axonal integrity below which visual function is damaged after optic neuritis (ON) is different between patients with multiple sclerosis (MS) and those without MS. Thinning of the inner retinal layers significantly correlated with visual impairment (assessed by mean deviation [MD] on visual fields tests) at final assessment. We identified a threshold of 75.4 μm for peripapillary retinal nerve fiber layer (pRNFL) thickness in MS patients, below which the MD is significantly worse. However, in ON not related to MS, a tipping point of 66 μm was determined for pRNFL, below which the visual function deteriorates abruptly, reflecting different pathological processes in MS and non‐MS.